PROTOTIPE ALAT PEMILAH BUAH KOPI OTOMATIS PADA PANEN RACUTAN (STRIPPING) MENGGUNAKAN SENSOR WARNA TCS34725 DAN MODUL ARDUINO - Irma Irma; Dedy Hendryadi; Juniarti Iryani (Journal System Information And Computer, 2024)
This study aims to sort coffee cherries based on color because of the different maturity levels and harvest times of coffee cherries. The garden owner for reasons of practicality will pick the coffee as a whole even if it is green or still raw all are picked (Stripping pick). Coffee cherries that have been picked must go through a sorting process based on color, this sorting is intended to produce coffee beans with good coffee quality and taste. This study uses action research methods. Researchers describe, interpret and explain a social situation at the same time and make changes or interventions with the aim of improvement or participation. The results of this study indicate that the prototype of an automatic coffee sorting tool using the TCS34725 made using an Arduino Uno, a TCS34725 sensor, an LDR sensor, two servos and an LCD. The input is in the form of an LDR sensor which detects the presence of coffee and a TCS34725 sensor which will read the RGB value of the coffee skin with Arduino Uno as a microcontroller to process the input so that it will produce output in the form of a servo which will rotate and the LCD displays information on the color of the coffee that has been processed. The TCS34725 sensor is implemented in a prototype of an automatic coffee sorting tool as a sensor that can read and determine the RGB value of the coffee skin. This prototype uses a small coffee object so that the TCS34725 takes a few seconds to get the ideal RGB value. RGB readings also affect the lighting around the sensor so constant light conditions are required.